9. ASSESSMENT OF STRESS STATUS BEFORE ELECTIVE THYROID SURGERY AT THE ONCOLOGY CENTER, HANOI MEDICAL UNIVERSITY HOSPITAL (Vietnam Journal of Community Medicine, 2025)
Objective: The study aimed to survey the stress status and find out some factors related to this status in patients before suffering from thyroid surgery.Subjects and methods: 150 patients before undergoing thyroid surgery were assessed for defining stress and the level of it based on the DASS-21 scale at the Oncology Center, Hanoi Medical University Hospital from July 2024 to October 2024.Results: The rate of patients with stress was 22%. The average stress score was 6.18 ± 6.9. Some psychological character, no health insurance and surgical method were factors related to stress, statistically significant difference with p < 0.05.Conclusion: The study showed that stress before elective thyroid surgery was quite high and there were many related factors of this condition. Medical staff need to pay much attention, promote health insurance and explain more clearly about surgical methods.
Keywords: Thyroid surgery, stress.